Characterising Saharan Dust Sources and Export using Remote Sensing and Regional Modelling - Schepanski, Kerstin (2009)
The PhD-thesis aims to characterise the Saharan dust cycle at diffent seasons using satellite remote sensing techniques and regional modelling studies. A dust index based on 15-minute infrared satellite measurements provided by the SEVIRI instrument onboard the Meteosat Second Generation (MSG) satellite is used to infer spatio-temporal charcteristics of dust sources north of 5°N over Africa since March 2006. The spatial distribution of dust sources points towards the importance of endorehic drainage systems in mountain areas. The temporal distribution of the time-of-day when dust mobilisation starts shows maximum activity during local morning hours, pointing towards the role of the breakdown of the nocturnal low-level jet. Details of the role and ability of the low-level jet breakdown for dust entrainment were studied using regional modelling. Furthermore, the seasonal dust export towards the tropical North Atlantic is considered using regional modelling.